Community participation within the context of recovery: multiple perspectives on South Asians with schizophrenia. Issue 2 (3rd April 2017) - Virdee, Gursharan; Frederick, Tyler; Tarasoff, Lesley A.; McKenzie, Kwame; Davidson, Larry; Kidd, Sean A.
ABSTRACT: Community participation is a key component of recovery for people with schizophrenia however, little is known about this process for persons of South Asian origin. This study explores the community participation and recovery amongst South Asians with schizophrenia living in Toronto, Canada. Seven people of South Asian origin with a diagnosis of psychosis or schizophrenia participated in a longitudinal qualitative study, with interviews taking place at three time points over 10 months. Nineteen service providers and community members were also interviewed in an effort to capture multi-level perspectives of persons of South Asian origin. Using a grounded theory approach we identified five major themes: (i) forces of collectivist community; (ii) religious and supernatural conceptualizations of schizophrenia; (iii) cultivating identity and belonging; (iv) points of exclusion; and (v) points of inclusion. The multi-level analysis provided insight into the many systems and structures that influence the recovery process, impacting identity, self-concept, and use of social space. Provider efforts to encourage community participation and recovery for persons of South Asian origin with schizophrenia should take into account individual identity and community of origin factors. Social and identity capital theories provide a mechanism to promote the social inclusion of individuals with schizophrenia.